Tertiary prevention strategies for micrometastatic lymph node cervical cancer: A systematic review and a prototype of an adapted model of care - Śniadecki, Marcin; Guani, Benedetta; Jaworek, Paulina; Klasa-Mazurkiewicz, Dagmara; Mahiou, Katia; Mosakowska, Karolina; Buda, Alessandro; Poniewierza, Patryk; Piątek, Olga; Crestani, Adrien; Stasiak, Maria; Balaya, Vincent; et al. (Critical reviews in oncology/hematology, 2024)
PURPOSE: We found a need for balancing the application of clinical guidelines and tailored approaches to follow-up of cervical cancer (CC) patients in the lymph node micrometastatic (MICs) setting. This review aimed to determine the current knowledge of management of MIC-positive CC cases. METHODOLOGY: We addressed prognostic and risk of recurrence monitoring impacts associated with MIC+ cases. The electronic databases for literature and relevant articles were analysed. RESULTS: Fifteen studies, (4882 patients), were included in our systematic review. While the results show that MICs significantly worsen prognosis in early CC. A tertiary prevention algorithm for low volume lymph node disease may stratify follow-up according to the burden of nodal disease and provide data that helps improve follow-up performance. CONCLUSION: MICs worsen prognosis and should be managed as suggested by the algorithm. However, this algorithm must be externally validated. The clinical impact of isolated tumor cells (ITC) remains unclear.
Keywords: lymfatické uzliny; Prevention; lokální recidiva nádoru; Tertiary Prevention; Lymph Nodes; Review; terciární prevence; Uterine Cervical Neoplasms; prognóza; nádory děložního čípku; Sentinel lymph node; Algorithm; Neoplasm Micrometastasis; Lymphatic Metastasis; Neoplasm Recurrence, Local; Micrometastasis; lidé; ženské pohlaví; Humans; Cervical cancer; Prognosis; lymfatické metastázy; Female; mikrometastázy